Clinical characteristics and predictive indictors of macrolide-unresponsive Mycoplasma pneumoniae pneumonia in children: a retrospective study - Li, Yun; Liu, Yunwei; Chen, Xinying; Xiao, Xiaolan; Chen, Yiting; Wang, Lianyu; Jiang, Wenwen; Yang, Jinghua (Frontiers in Pediatrics, 2024)
Introduction: Macrolide-unresponsive Mycoplasma pneumoniae pneumonia (MUMPP) cases have been rapidly increasing. The primary reason for this increased incidence is the pathogen's acquisition of resistance through mutations in 23S rRNA genes. Due to the unfeasibility of testing for macrolide susceptibility at the time of admission, this study aimed to assess the clinical features of pediatric MUMPP, using insights from laboratory tests and patterns of chest radiographic resolution.Material and Methods: We conducted a retrospective review of 161 patients with M. pneumoniae pneumonia (MPP) between January 2023 and December 2023. These patients were categorized into two groups based on their responsiveness to macrolides: 72 patients were in the MUMPP group, and 89 patients were in the macrolide-sensitive Mycoplasma pneumoniae pneumonia (MSMP) group.Results: MUMPP patients experienced a longer duration of fever and hospital stay. A higher proportion of MUMPP patients had shortness of breath, transcutaneous blood oxygen saturation (SpO2) lower than 94%, bilateral lobar infiltrates, lobar pneumonia and pleural effusion. The serum level of serum ferritin (SF), interleukin-6(IL-6), D-dimer, lactate dehydrogenase to albumin rate (LAR), and neutrophil to lymphocyte rate (NLR) were higher in MUMPP group.Conclusions: Our findings revealed that patients with MUMPP exhibit more severe initial radiographic indicators and clinical course compared to those with MSMP. Therefore, it is crucial to promptly administer alternative therapeutic agents besides macrolides for the management of MUMPP.